2015
DOI: 10.3762/bjnano.6.29
|View full text |Cite
|
Sign up to set email alerts
|

Tunable white light emission by variation of composition and defects of electrospun Al2O3–SiO2 nanofibers

Abstract: SummaryComposite nanofibers consisting of Al2O3–SiO2 were prepared by electrospinning in combination with post-calcination in air. X-ray diffraction, scanning electron microscopy, and transmission electron microscopy were used to investigate the crystalline phase and microstructure of the composite nanofibers. Photoluminescence experiments indicated that the resulting white light emission can be tuned by the relative intensity of the individual spectral components, which are related to the individual defects s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…To correlate the oxygen vacancy (OV) with the emission behavior, the compound was further annealed under vacuum atmosphere. Earlier reports on different matrixes showed that a change in the metal ion’s composition ratio may lead to a change in the PL behavior . In the present case, to investigate any change in the PL behavior, we have slightly changed the ratio such as and from that ideal 1 / 2 ratio in the pure spinel.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…To correlate the oxygen vacancy (OV) with the emission behavior, the compound was further annealed under vacuum atmosphere. Earlier reports on different matrixes showed that a change in the metal ion’s composition ratio may lead to a change in the PL behavior . In the present case, to investigate any change in the PL behavior, we have slightly changed the ratio such as and from that ideal 1 / 2 ratio in the pure spinel.…”
Section: Introductionmentioning
confidence: 93%
“…Earlier reports on different matrixes showed that a change in the metal ion's composition ratio may lead to a change in the PL behavior. 35 In the present case, to investigate any change in the PL behavior, we have slightly changed the Mg Al ratio such as 0.98 2 and 1 1.96 from that ideal 1 / 2 ratio in the pure spinel. Large variation of the Mg Al ratio from the ideal ratio may lead to formation of binary systems such as MgO−Al 2 O 3 composite or a mixture consists of several phases such as MgAl 2 O 4 , MgO, Al 2 O 3 , and so on.…”
Section: +mentioning
confidence: 99%
“…The phenomenon indicates that the binding energy and stability of the functional group, Al–O, become greater, which is consistent with the result reported by Madroñero et al Besides the fact that the bands around 690 cm –1 of synthetic sorbents are assigned to the Al–O bond, it can be seen that the depth of the bands becomes more pronounced as the high alumina cement content increases, which indicates that C 12 A 7 content increases with the increase of the high alumina cement. The band located at 1120 cm –1 is speculated to be caused by two factors: one is attributed to O–Si–O bending of the SiO 4– group; the other indicates the formation of the Al–O–Si bond. , These vibrational modes appear at frequencies relatively close to each other due to the similar mass of Si and Al atoms. The existence of SiO 4– is probably due to a minor constituent of SiO 2 in carbide slag.…”
Section: Resultsmentioning
confidence: 99%
“…The band located at 1120 cm −1 is speculated to be caused by two factors: one is attributed to O−Si−O bending of the SiO 4− group; the other indicates the formation of the Al− O−Si bond. 50,51 These vibrational modes appear at frequencies relatively close to each other due to the similar mass of Si and Al atoms. The existence of SiO 4− is probably due to a minor constituent of SiO 2 in carbide slag.…”
Section: Methodsmentioning
confidence: 96%
“…The obtained nanofibers were heat‐treated at 1200 °C in the air to remove polymer and to produce mullite and cristobalite nanocrystals. The experiments indicated that the prepared materials could be used as catalysts, coatings, and microelectronics devices . Su et al synthesized aluminosilicate nanotubes by combining the sol‐gel method with electrospinning of a PVA solution.…”
Section: Introductionmentioning
confidence: 97%